A Case Report on Unilateral Double Testicles - Paul, AC; Hassan, MK; Alam, MJ; Biswas, SK; Saha, AK; Mridha, NI (Faridpur Medical College Journal, 2011)
A unilateral double testicle is a rare anomaly characterized by migration of one testicle towards the opposite inguinal canal. The commonest erratic development is the more or less incomplete descent of the testicle along the normal route of descent, which is known as cryptorchidism. In ectopia of the testicles, as opposed to cryptorchidism, the displaced testicle does not descend along the usual route but as it migrates downwards it moves into an entirely abnormal position. Usually the migrating testicle remains on its own side of the body but may end up in an unusual position e.g. in the superficial tissue of the inguinal region above the external ring, in the area of the base of the penis, in the upper part of the thigh, in the region of perineum or in the pelvic cavity. In this case, the right and left testicles were found to descend together on the right side, whereas the left side of the scrotum was entirely empty. The case was treated with 'Bilateral Transeptal Subdartos Orchidopexy'. The case reported here is evidently one of extreme rarity as there are about 148 reported cases since the first described by Von Lenhossek in1886. Key words: Cryptorchidism; Testicle; Ectopia; Orchidopexy; CTE. DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9214 FMCJ 2011; 6(2): 110-112